Dietary sodium butyrate supplementation during mid-to-late gestation enhances reproductive performance and antioxidant capability in sows - C.L. Lu; Z.F. Fang; L.Q. Che; Y. Lin; S.Y. Xu; Y. Zhuo; L. Hua; J. Li; X.M. Jiang; M.M. Sun; Y.Z. Huang; D. Wu; et al. (Animal)
Sodium butyrate (NaB) has been used as a feed additive in livestock production due to its antioxidant and anti-inflammatory properties. However, the effect of dietary NaB supplementation during mid− to late gestation on the reproductive performance of sows remains unclear. Thirty-two pregnant sows (Landrace × Yorkshire) at two or three parities were divided into two groups based on similar BW and backfat thickness on day 30 of pregnancy. The control group received a normal gestational diet, while the NaB group was fed a NaB-supplemented diet, of which 2 g/kg corn was replaced with an equal weight of NaB. Sows were fed an experimental diet from day 30 to day 114 of gestation and the same diet during lactation. The reproductive performance, antioxidant, and anti-inflammatory capabilities of sows were analysed. Gestational supplementation of NaB tended to increase the total litter size (P = 0.069) and the number of piglets born alive (P = 0.052), significantly improve placental efficiency (P = 0.049), and increase feed intake during lactation (P = 0.004). Additionally, the stillbirth rate (P = 0.051) tended to be decreased by gestational NaB supplementation. NaB supplementation enhanced the antioxidant capacity of sows, as evidenced by increasing serum T-SOD activity on day 60 of gestation (P < 0.01) and CAT activity on the day of farrowing (P < 0.05), along with reduced serum malondialdehyde concentration on day 90 of gestation (P < 0.05), as compared to control group. Additionally, NaB supplementation tended to decrease serum 8-OHDG concentration on day 60 of gestation (P = 0.064), and increased serum concentrations of short-chain fatty acids (P < 0.05). Taken together, gestational sodium butyrate supplementation might enhance reproductive performance and antioxidant capability in sows. Thus, NaB is a potential additive for improving reproductive performance in sows.